Proton radiography of intense-laser-irradiated wire-attached cone targets - Yabuuchi, T; Sawada, H; Bartal, T; Batani, D; Gizzi, L; Key, M; MacKinnon, A; McLean, H; Norreys, P; Patel, P; Stephens, R; Spindloe, C; et al. (2011)
Measurements of extreme electrostatic and magnetic fields are of interest for the study of high-energy-density plasmas. Results of proton deflectometry of cone-wire targets that are of interest to fast-ignition inertial confinement fusion are presented. © 2006 IEEE.